Teacher Candidates' Awareness and Acceptance of Diversity - Lori Cook-Benjamin; Beth Walizer; Keith Dreiling (The Advocate, 2013)
Introduction: Like many colleges of education and the departments within them, concerns exist on the best way to provide teacher candidates with clinical (also referred to as “field” in the literature) based experiences that meet accreditation outcomes. In the Report of the Blue Ribbon Panel on Clinical Preparation and Partnerships for Improved Learning (NCATE, 2010), members of the panel stressed the importance of using a “clinically based model” for teacher preparation.